Effect of Protein Restriction During Mid-to Late Gestation of Beef Cows on Female Offspring Fertility, Lactation Performance and Calves Development - Lopez Valiente, Sebastian; Maresca, Sebastian; Rodriguez, Alejandro Martin; Long, Nathan M.; Quintans, Graciela I.; Palladino, Rafael Alejandro (E-Cronicon, 2022)
Cow calf operation in Argentina are managed under extensive grazing condition and the quality of forages is often poor during second half of gestation. Protein restriction in bovine gestation affects production traits in progeny. The present work investigated the effects of two levels of crude protein (CP) provided to mature dams during late gestation on subsequent heifer’s growth postweaning, reproductive performance, milk production and grand offspring evolution. At 121 d prepartum, 68 multiparous Angus cows were randomly assigned to low protein (LP, 6% CP) or high protein (HP, 12% CP) at 12 pens per treatment group. Following calving, all cow/calf pairs were housed together until weaning, then female progeny were removed and maintained on pasture as a single group. At puberty (P = 0.01) and pregnancy determination (P = 0.05) the HP heifers were heavier than LP heifers. The LM area was greater at 20 mo of age in HP compared to LP heifers (P = 0.01) and the HP heifers had greater 12th rib fat thickness at 30 and 35 mo of age (P = 0.02). Serum IGF-1 concentration was greater in HP heifers compared to LP heifers (P = 0.05). No dam nutrition effects were found on offspring age at puberty (P = 0.98), final pregnancy rate (P = 0.28) or milk yield (P = 0.76) but heifers born to LP dams had greater milk protein percentage (P = 0.04) and tended to produce increased milk fat percentage (P = 0.08) compared with HP heifers. The LP grand offspring grew faster from birth until weaning compared with HP grand offspring (P < 0.01) with reduced insulin concentrations (P = 0.03) and tended to have increased glucose concentrations than HP calves (P = 0.09). Protein supplementation during late gestation does not affect reproductive performance of the offspring heifers but did impact their BW evolution, milk quality and grand offspring performance. Implications: The use of diet with low amount of protein which the female fetus is exposed in utero can affect her subsequent development and ability to nourish subsequent generations.